Pengaruh Layanan Bimbingan Klasikal dengan Metode Experiential Learning terhadap Adaptabilitas Karier Siswa Kelas XI SMA Negeri 2 Ungaran - Nandya Ayu Larasati; Desi Maulia; Ismah Ismah (Universitas Mathla'ul Anwar Banten, 2026)
Career adaptability is an essential competency for students in responding to changes in the world of work, particularly in the era of digital transformation and artificial intelligence. This study aimed to examine the effect of classical guidance services using the experiential learning method on the career adaptability of eleventh-grade students at SMA Negeri 2 Ungaran. The study employed a quantitative approach with a quasi-experimental design using a pretest–posttest control group design. The participants consisted of 71 students, comprising 36 students in the experimental group and 35 students in the control group, selected through cluster random sampling. Data were collected using a career adaptability scale covering four dimensions: concern, control, curiosity, and confidence. Data analysis was conducted using an independent sample t-test. The results revealed a significant difference between the experimental and control groups, with a significance value of 0.001 (p < 0.05). The mean score of the experimental group increased from 99.28 in the pretest to 112.25 in the posttest, indicating an improvement in students’ career adaptability after receiving the intervention. These findings suggest that classical guidance services based on experiential learning are effective in enhancing students’ career adaptability. Therefore, experiential learning can be considered an innovative and practical approach for school counselors in preparing students to face future career challenges.